Long vs. short: understanding the dynamics of persistent summer hot spells in Europe - D. Pappert; D. Pappert; A. Tuel; D. Coumou; M. Vrac; O. Martius; O. Martius; O. Martius (Weather and Climate Dynamics, 2025)
The persistence of surface hot spells in Europe on subseasonal timescales can lead to significant socio-economic impacts. Here, we adopt a regional perspective to compare the dynamical features associated with long-lasting persistent (12–26 d) and short-lived (4–5 d) regional-scale hot spells in Europe during summer using the ERA5 reanalysis. We identify six coherent regions in Europe (Southwestern (SW) Europe, Western (W) Europe, Central-Southern Europe, Northern Europe, Eastern Europe, and Northwestern Russia) defined by the clustering of grid cells that experience hot spells at the same time. Temperatures are spatially averaged within each region to identify hot spells; the analysis specifically concentrates on events occurring in SW and W Europe.